A Highly Sensitive Nonenzymatic Glucose Sensor Based on Carbon Electrode Amplified with PdxCuy Catalyst. Issue 3 (26th January 2021) - Chowdhury, Sreya Roy; Mukherjee, Parthasarathi; Bhattacharya, Swapan Kumar
Abstract: Approximately global Pd and Pd94 Cu6 alloy nano catalysts of average diameter 10.5 and 5.9 nm respectively, have been synthesized hydrothermally by wet chemical reduction and co‐reduction methods without addition of any capping agent. X‐ray diffraction and various microscopic studies are used to characterize the crystal phase and the morphology of the catalysts. Non‐enzymatic amperometric glucose sensors based on these synthesized catalyst materials are tested and compared in alkali at different potentials by cyclic voltammetry and chronoamperometry. The sensors characterized by fixed potential chronoamperometry are found to be sufficiently sensitive to glucose at different negative potentials like −0.65 V, −0.40 V, −0.10 V with respect to Hg/HgO electrode (E 0 ≈0.1 V), where the reactions of glucose oxidation are different. The sensor constructed with Pd94 Cu6 nanocatalyst shows an outstanding sensitivity of 10.1 mA cm −2  mM −1 which is considerably higher than that constructed with similarly synthesized Pd nanoparticles at any potential and that found in the literature of Pd based glucose sensors. The lower detection limit and response time obtained with Pd94 Cu6 nanoparticles are 10 μM and 3 s respectively. These sensors also exhibit high specificity to glucose and significant anti‐interference property against some common species like ascorbic acid (AA), uric acid (UA) and some monosaccharides whose interfering effects are found to decrease with decrease of potential of glucose oxidation. The electrocatalytic ability of the synthesized Pd and Pd94 Cu6 nanoparticles toward glucose oxidation has also found promising in blood sample at different potentials. Abstract :